Back up: Can users sue platforms to reinstate deleted content? - Matthias C. Kettemann; Anna Sophia Tiedeke (Internet Policy Review, 2020)
A private order of public communication has emerged. Today, social network services fulfill important communicative functions. A lot has been written about the failings of companies in deleting problematic content. This paper flips the question and asks under which conditions users can sue to reinstate content and under which circumstances courts have recognised "must carry" obligations for social network services. Our analysis, an initial comparative analysis of case law on the reinstatement of user-generated content, will point to a larger issue of systemic relevance, namely the differences in treatment of states and private companies as threats to and/or guarantors of fundamental rights in the United States and in Germany. It is a contribution to the important debate on the interaction of states and platforms in governing online content.
Keywords: 300; Platforms; Intermediaries; Private spaces; Courts; Indirect application of human rights